Fire safety engineering principles applied to a multi-storey steel building. Issue 9 (11th September 2021) - Possidente, Luca; Weiss, Alessandro; de Silva, Donatella; Pustorino, Sandro; Nigro, Emidio; Tondini, Nicola
Abstract : In this paper, fire safety engineering principles were applied to a steel-framed office building. The case study consisted of a 15-storey steel moment-resisting frame designed in Japan. Once the performance criteria had been defined, two severe fire scenarios for the unprotected structure, implying a different degree of building collapse, were identified and modelled in zone models, OZone and consolidated fire and smoke transport (CFast), as well as in the computational fluid dynamics software Fire Dynamics Simulator (FDS). Based on the results of the fire development simulation, several finite-element thermo-mechanical analyses were performed with SAFIR. OZone and CFast models, which are much less computationally demanding, provided comparable failure mode and time with respect to FDS. Since the steel frame was seismically designed as a moment-resisting frame in the two main horizontal building directions, the columns were particularly stocky. Moreover, they were only partially heated because they were located on the compartment edges. For these reasons, columns did not exhibit failure, in contrast to the assumptions taken in the risk-ranking process in relation to the evaluation of the consequences, suggesting a revision of such estimations and a possible iterative procedure for the definition of critical fire scenarios for the structure.